Mapeamento das áreas de preservação permanente hídricas de acordo com a lei nº 12.727, de 17 de outubro de 2012 - Nascimento, Kleberson Rodrigo do (2019)
The present study is focused on Permanent Preservation Areas (PPAs) of water bodies, which are vegetation strips around water bodies that serve as soil stabilization mechanisms and prevent suspended residues from reaching the riverbed. With the intention of improving aspects of environmental preservation and regulation mechanisms of the current legislation, this study designed two geographic models, one that determines the width of the watercourses in the region under study and another that identifies the native vegetation using remote sensing. Through the resulting relationship between the two models, a symmetrical analysis of the data was carried out, determining the remaining forest cover and areas with deficit of tree vegetation, which must be reforested in order to comply with the guidelines of the Brazilian Forest Code, Law No. 12,727, of October 17, 2012. The techniques used the QGIS geoprocessing software for watershed characterization and the Google Earth Engine cloud processing platform for supervised image classification from Sentinel-2 satellite MSI sensor images. To increase the viability of the research, the use of free software and open data was preferred in most of the processes. The research resulted in two articles with Western Paraná as the study area. Article 1 resulted in mapping the hydrography and its respective widths, thus establishing an average total area of 299.9 km² of rivers with a length of 28,275.42 km. Based on the legislation, the Ideal Permanent Preservation Areas for the study territory was determined as 2,622.54 km². In Article 2, 5,954.33 km² of tree cover were classified and it was estimated that there is 812,98 km² of deficit in water APPs in the region under study.